Mecanismos químicos de resistência em meloeiro à mosca-minadora, Liriomyza sativae Blanchard 1938 (diptera: agromyzidae) - Vasconcelos, Jéssica Fontes (2020)
The leaf miner fly, Liriomyza sativae Blanchard (Diptera: Agromyzidae) is the main pest of the culture of melon (Cucumis melo L.). The control of this pest is carried out with the use of synthetic insecticides. However, the lack of rotation of active ingredients and the indiscriminate application of insecticides, may entail the selection of resistant organisms. The use of resistant plants is a relevant technique that can bring good results for pest control. The study of volatile plant compounds that act in plant defense repelling the insect pest (direct defense) creates new perspectives for the use of these substances in management strategies. The presence of phenolic compounds in melon genotypes can characterize the discovery of genotypes resistant to L. sativae. Thus, the objective of this work was: a) to evaluate whether the volatile compounds released by melon genotypes interfere in the attractiveness and repellency of L. sativae and b) to characterize the phenolic compounds of the melon genotypes, as well as the antibiotic action of those on L. sativae. A four-arm olfactometer was used, supplying to the insect through the plant “in vivo”, the odor of constitutive volatiles of different melon genotypes. For the characterization of volatile compounds, solid-phase microextraction was used. Extracts of melon leaves were submitted to ultra-efficient liquid chromatography associated with mass spectrometry for the delineation of phenolic compounds. Melon plants were infested with L. sativae and later assessments of larval and pupal viability were made. The volatiles of melon genotypes CNPH 06-1047-343, CNPH 06-1047-333 e CNPH 06-1047-341, were unattractive to L. sativae, while volatiles from the commercial Goldex hybrid and genotype CNPH 11-1071-43 were more attractive. Through the analysis of volatile profiles, it was possible to identify the compounds, acetic acid, (Z) -3-hexen-1-ol, α-pinene, (Z) -β-ocimene, (E) -β-ocimene, linalool, allo-ocimene and neo-allo ocimene. It is concluded that the melon genotypes CNPH 06-1047-343, CNPH 06-1047-333 and CNPH 06-1047-341 present resistance characteristics due to the non-preference of L. sativae on account of the lower amount of volatiles and the higher concentration of acetic acid in its volatile composition. Concerning to the phenolic composition of the chemical profiles, the compounds hydroxybenzoic-hexoside acid, ferulic acid and trihydroxy octa ecadienic acid were identified. The lowest larval and pupal viability were observed in CNPH 06-1047-333. The melon genotypes CNPH 06-1047-333 and CNPH 06-1047-341 presented, respectively, the highest and lowest levels of total phenolics, but there were no differences regarding the larval and pupal viability of L. sativae, indicating the lack of relation between total phenols and antibiotic resistance of melon genotypes to L. sativae. According to the analysis of volatile and phenolic compounds, CNPH 06-1047-343, CNPH 06-1047-333 e CNPH 06-1047-341 genotypes are less attractive to L. sativae than the commercial hybrid Goldex and CNPH 11-1071-43.